Development of Animation-Based Learning Videos on the Material of the Proclamation of Independence Events to Increase Students' Interest in Learning History for Class XI IPS at As-Shofa Islamic High School - Liadiani, Cut; Isjoni, Isjoni; Asril, Asril (CV. Rayyan Dwi Bharata, 2025)
This study discusses the development of animation-based learning videos on the material of the proclamation of independence events to increase students' interest in learning history in class XI IPS at As-Shofa Islamic High School. This study aims to determine how the process of developing animation-based learning videos on the material of the proclamation of independence events for class XI IPS at As-Shofa Islamic High School, then to determine the feasibility of using animation-based learning videos on the material of the proclamation of independence events for class XI IPS at As-Shofa Islamic High School and to determine the increase in students' interest in learning the material of the proclamation of independence events in history learning for class XI IPS at As-Shofa Islamic High School by using animation-based learning videos. This study uses a research and development method or Research and Development (RD) with data collection techniques in the form of observation, documentation, tests, questionnaires. The subjects in this study were 32 students of class XI IPS 1 and 6 students of class XI IPS 2. Based on the results of the assessment carried out by material experts, the overall percentage obtained was 94.5% with the category